Creative industries or industrialisation of creativity? Craft labour and the uneven and combined development of capital. (Publicatio UEPG: Ciências Sociais Aplicadas, 2019)
The objective of this article is to demonstrate the spread of the classification of the so-called "creative industries" which conceals a neoliberal process of direct and indirect subordination of creative labour to capital. In this way, craft labour and its production and reproduction through the uneven and combined development of capital are used as an example of analysis. Consequently, in the first part the problematic is defined the neoliberal hegemonic term of creative industry, to differentiate it from a political and economic process of industrialisation of creativity, specifying the relationship with the craft labour. Then, the relationship of direct and indirect subordination of craft labour in Europe and Latin America is defined in a general way, in order to clarify their differences presented by the social division of labour. Finally, an analysis of the uneven and combined movement is made, to explain the relations and trends of distinction and equalisation between and within countries.